2013
DOI: 10.1097/nmc.0b013e3182836af7
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a Care Delivery Model to Increase Breastfeeding

Abstract: This article describes the process of changing the care delivery model for maternity practice in a New York State Regional Perinatal Center to support exclusive breastfeeding, defined as providing nothing other than human milk feedings. Barriers exist in hospitals that inhibit exclusive breastfeeding of newborns at the time of discharge and fail to meet the recommendations outlined by the World Health Organization and New York State Department of Health. All aspects of mother/baby care were evaluated to meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Participants shared examples of professional resistance (by physicians, nurses, and administrators) to adopting evidence-based breastfeeding supportive practices, also identified in other studies (Magri & Hylton-McGuire, 2013;Nickel, Taylor, Labbok, Weiner, & Williamson, 2013). A study about the adoption of breastfeeding best practice guidelines similarly found varying groups of nurses who were identified as "eager adopters," "fence sitters," and "the old guard."…”
Section: Indirect Barriersmentioning
confidence: 76%
“…Participants shared examples of professional resistance (by physicians, nurses, and administrators) to adopting evidence-based breastfeeding supportive practices, also identified in other studies (Magri & Hylton-McGuire, 2013;Nickel, Taylor, Labbok, Weiner, & Williamson, 2013). A study about the adoption of breastfeeding best practice guidelines similarly found varying groups of nurses who were identified as "eager adopters," "fence sitters," and "the old guard."…”
Section: Indirect Barriersmentioning
confidence: 76%
“…Some suggested clinical implications from the New York State program mirrored those mentioned here, including the necessity of active leadership, collaborative sharing to maintain momentum in implementing changes, and the importance of online education. 24 Although the authors were not able to find published results from the other LCs discussed in this work, it is significant that several existing projects offer extensive online resources. 3,15 For example, Birth and Beyond California offers resources for training decision makers, staff, and trainers; resources for initiating and managing hospital quality improvement teams and regional networks; and evaluation materials.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain BFH Designation, hospitals must adhere to all 10 of the practices or steps; step number seven is “enable mothers and their infants to remain together and to practice rooming-in 24 hours a day” (Baby-Friendly USA, 2022, p. 1), in part due to the premise that this practice promotes early breastfeeding and maternal–infant bonding. For example, in one hospital, after changes in their maternity care model as part of a New York state perinatal quality improvement project, when rooming-in increased from 0% to 70%, the exclusive breastfeeding rate increased from 6% to 44% during the inpatient postpartum stay (Magri & Hylton-McGuire, 2013). Cohen et al (2018) in a quantitative meta-analysis reported maternal–infant dyad connection as one of the six high-impact factors associated with both increased breastfeeding initiation and breastfeeding continuation.…”
mentioning
confidence: 99%